Application of Intraoperative Neurophysiological Monitoring: New insights - Gurung, Pritam; Dabadi, Sambardhan; Raj Dhungel, Raju; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Various intraoperative neurophysiological monitoring (IONM) helps in assessing the integritry of neural pathways during the surgical treatment. IONM is an assistive tool to preserve the fuction of brain, brainstem, cranial nerve, spinal cord and peripheral nerves and a great assest for neurosurgeons. Different application of IONM includes: MEP, SSEP, ABR, VEP, BCR and AMR. Intraoperative neuromonitoring has become an integral part of the neurosurgery and is being routinely used in various operative cases. This paper discusses the application and benefit of IONM, with its role in delivering a high quality intra operative care to detect and prevent neurological deficits.